Efectos del cambio de uso del suelo y su proyección futura en la erosión hídrica en los cantones Zapotillo y Pindal, provincia de Loja - Morocho Lalvay, Mayra Janeth (2019)
This research was developed in the cantons “Zapotillo and Pindal” of Loja province, where the Revised Universal Soil Loss Equation (RUSLE) was applied through ArcGIS and the TerrSet software in order to determinate the effects of land use change from the period 1983 to 2012 and its future projection of water erosion. The land use changes were determined with cartographic information generated by CINFA and CITIAB. Additionally, future scenarios of land use changes were generated using the Land Change Modeler tool of the TerrSet software. Subsequently, susceptibility areas to water erosion were estimated using erosivity information of rain; soil erodibility, slope length and steepness (DEM with 30 m resolution); and vegetation cover. The agricultural land category increased 10 758 ha while the dense dry forest cover decreased 10 375 ha from 1983 to 2012. For the year 2030, the probabilities of change predict that 31.65% of the dense dry forest will represent a high probability; followed by the semi-dense dry forest where 32.5% will represent a very high probability as while as the desert scrub and the semi-dense dry scrub will have a very low probability of change. The results of erosion show values ranging from 0 to 200 t/ha/year, predominantly erosion rates from 0 to 10 t/ha/year (Very low), which covers 71.76% (101 629 ha) for 1983 of the study area; compared to 64.53% (91 390 ha) in 2012. Finally, 59.65% (84 480 ha) of total area presents losses of 0–10 in the year 2030. This indicates that the study area has a very low susceptibility to water erosion due to the presence of conservation areas; however, it is evident a decrease in erosion rates with a very low category due to the increase of agricultural activities. Keywords: land use change, future scenarios, water erosion, RUSLE